Unusual poles of the ζ-functions for some regular singular differential operators - Falomir, Horacio Alberto (2003)
We consider the resolvent of a system of first-order differential operators with a regular singularity, admitting a family of self-adjoint extensions. We find that the asymptotic expansion for the resolvent in the general case presents powers of λ which depend on the singularity, and can take even irrational values. The consequences for the pole structure of the corresponding ζ- and η-functions are also discussed.